2017
DOI: 10.1021/acs.nanolett.7b02128
|View full text |Cite
|
Sign up to set email alerts
|

Optical Manipulation of Rashba Spin–Orbit Coupling at SrTiO3-Based Oxide Interfaces

Abstract: Spin-orbit coupling (SOC) plays a crucial role for spintronics applications. Here we present the first demonstration that the Rashba SOC at the SrTiO-based interfaces is highly tunable by photoinduced charge doping, that is, optical gating. Such optical manipulation is nonvolatile after the removal of the illumination in contrast to conventional electrostatic gating and also erasable via a warming-cooling cycle. Moreover, the SOC evolutions tuned by illuminations with different wavelengths at various gate volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 67 publications
3
56
0
Order By: Relevance
“…WAL is usually considered as an indication of strong spin–orbit coupling. [ 15,37 ] WAL persists up to ≈30 K and the magnetoconductance curves can be fitted by the Hikami–Larkin–Nagaoka (HLN) model [ 38 ] ΔσB=ae2πh[]1nBϕBψ12+BϕB…”
Section: Figurementioning
confidence: 99%
“…WAL is usually considered as an indication of strong spin–orbit coupling. [ 15,37 ] WAL persists up to ≈30 K and the magnetoconductance curves can be fitted by the Hikami–Larkin–Nagaoka (HLN) model [ 38 ] ΔσB=ae2πh[]1nBϕBψ12+BϕB…”
Section: Figurementioning
confidence: 99%
“…Light illumination can generate electron–hole pairs, which not only can contribute to the conductivity but also affect the diffusion of oxygen vacancies and thereby significantly modify the transport properties . For example, tunable persistent photoconductivity (PPC) has been reported in STO‐based heterointerfaces and combining light illumination with a gate bias, an enhancement of the resistance gatability has been demonstrated . In this section, we review the optical tunability and the underlying physical mechanisms.…”
Section: Light/matter Interactionmentioning
confidence: 99%
“…Encouraged by the tunability of this joint effect where gate bias is combined with light illumination, Cheng et al demonstrated that the quantum states could also be tuned via a gating effect by light at the STO‐based interfaces, as shown in Figure . The transition from WL to WAL implies that the Rashba spin‐orbit coupling is tunable by the light illumination with different wavelengths (470 and 940 nm) . In contrast to the conventional electrostatic gating at low temperatures (see Section ), this optical manipulation is nonvolatile and the tunability of the spin‐orbit coupling persists after turning off the light.…”
Section: Light/matter Interactionmentioning
confidence: 99%
See 2 more Smart Citations